2016
DOI: 10.1021/jacs.6b02954
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Tools To Monitor and Manipulate Adaptive Immune Responses

Abstract: Methods to monitor and manipulate the immune system are of enormous clinical interest. For example, the development of vaccines represents one of the earliest and greatest accomplishments of the biomedical research enterprise. More recently, drugs capable of “reawakening” the immune system to cancer have generated enormous excitement. But, much remains to be done. All drugs available today that manipulate the immune system cannot distinguish between “good” and “bad” immune responses and thus drive general and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 129 publications
(319 reference statements)
0
13
0
Order By: Relevance
“…Immune responses could play double-edged roles, with a good role of fighting off invading organisms and a bad role of causing autoimmune diseases. 42 Our platform could screen for molecules that may strengthen antibody-antigen interaction to avoid immune escape of antigens, or block epitopes that inhibit innate immune attack in autoimmune diseases. Also, this versatile platform could be used to screen epitope or antibody mimics; 3) screening for imaging agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune responses could play double-edged roles, with a good role of fighting off invading organisms and a bad role of causing autoimmune diseases. 42 Our platform could screen for molecules that may strengthen antibody-antigen interaction to avoid immune escape of antigens, or block epitopes that inhibit innate immune attack in autoimmune diseases. Also, this versatile platform could be used to screen epitope or antibody mimics; 3) screening for imaging agents.…”
Section: Discussionmentioning
confidence: 99%
“…5) assisting in genome editing: although genome editing is a powerful tool to manipulate disease conditions, the gene associations of some diseases are still elusive, such as the majority of late onset Alzheimer's disease; 43 therefore, epitope editing (immune editing) could be an important complement in genome editing. 42 The SPEED strategy also has certain limitations. For example, prior knowledge of epitope region within an antigen is needed and the corresponding antibodies should be available.…”
Section: Discussionmentioning
confidence: 99%
“…With this approach the authors are able to identify and further develop sequences or peptidomimetics that bind in the low nanomolar range. These approaches and their subsequent application in therapy and diagnostics are described at length in Doran et al [46]…”
Section: Epitope Predictionmentioning
confidence: 99%
“…Redirecting these antibodies to target specic disease cells could lead to adaptive immunities for selective and effective therapy. [31][32][33][34][35][36][37] For instance, a pioneering work from McNaughton's group demonstrated that DNP-modied nanobody 5F7 could recruit anti-DNP antibodies to HER2 + cancer cells and elicit a specic ADCC effect in vitro. However, no in vivo studies have been reported yet.…”
Section: Introductionmentioning
confidence: 99%